2015
DOI: 10.1515/bglass-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular coating on curved alumina substrates using a novel bioactive and strong glass-ceramic

Abstract: Abstract:In the last few years, optimal fixation of orthopaedic implants evolved to preserve host bone and enhance tissue integration by surface modifications, including the use of coatings with bioactive ceramics. In this work, we fabricated a novel bone-like porous bioactive glass-ceramic coating on curved alumina substrates; good joining between the two components was possible due to the interposition of a glass-derived dense interlayer. The mechanical properties of the porous glass-ceramic, which mimics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…2a) [53,54], while the outer trabecular coating was successfully produced by properly adapting the sponge replica method to the 3D radial geometry of the prosthesis (Figs. 2b and 2c) [55][56][57]. In these studies, the issue of estimating reliably the adhesion strength of the bioactive coating to the curved substrate was also tackled: specifically, the recommendations of the relevant ASTM standard dealing with pull-out tests on flat samples [58] were properly adapted for a "nearly-flat" geometry and appropriate testing tools were manufactured for this purpose [53].…”
Section: Orthopaedic and Dental Implantsmentioning
confidence: 99%
“…2a) [53,54], while the outer trabecular coating was successfully produced by properly adapting the sponge replica method to the 3D radial geometry of the prosthesis (Figs. 2b and 2c) [55][56][57]. In these studies, the issue of estimating reliably the adhesion strength of the bioactive coating to the curved substrate was also tackled: specifically, the recommendations of the relevant ASTM standard dealing with pull-out tests on flat samples [58] were properly adapted for a "nearly-flat" geometry and appropriate testing tools were manufactured for this purpose [53].…”
Section: Orthopaedic and Dental Implantsmentioning
confidence: 99%
“…1). Previous studies demonstrated the feasibility of this device in a flat geometry [26,27] and in a simplified curved configuration [28][29][30]; the challenge presented in this work is to develop a processing schedule to produce a real, complete prototype such as the one depicted schematically in Fig. 1, which also was the main objective of the EC-funded project MATCh.…”
Section: Introductionmentioning
confidence: 99%
“…This composition was then discarded with respect to such applications, as the high content of SiO 2 and the significant presence of Al 2 O 3 resulted in an almost inert behavior with almost no apatite-forming capability in contact with biological fluids, thereby preventing the formation of a tight bond to bone. However, the material was found highly suitable to produce porous orbital implants [20], which must elicit minimal or no reactions in contact with ocular tissues [21], and multilayer coatings onto ceramic implants [22].…”
Section: Resultsmentioning
confidence: 99%